Endothelial cell apoptosis - Kolesnick, Richard (Henry Stewart Talks, 2007)
Endothelial apoptosis, Role in tumor response to radiation therapy, Tissue damage results from depletion of stem cells and cells with clonogenic capacity, Radiation targets the DNA leading to reproductive (mitosis-associated) or apoptotic cell death, Modifications of DNA damage recognition and repair pathways determine the level of tissue sensitivity to radiation, Sphingomyelin, Ceramide, GI tract and bone marrow: very radiation responsive, Growth patterns of tumors, The two-target model for single-dose radiotherapy of experimental tumors, Engaging the vascular component of tumor response to radiation